2015
DOI: 10.1016/j.ijcard.2015.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cardiometabolic risk factors in the Southern Cone of Latin America: A population-based study in Argentina, Chile, and Uruguay

Abstract: Background Cardiovascular disease is a major cause of death, and its mortality is increasing in Latin America. However, population-based data on cardiovascular disease risk factors are sparse in these countries. Methods A total of 7,524 men and women, aged 35 to 74 years old, were recruited between February 2010 and December 2011 from randomly selected samples in 4 cities (Bariloche and Marcos Paz, Argentina; Temuco, Chile; and Pando-Barros Blancos, Uruguay) in the Southern Cone of Latin America. Cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 29 publications
6
61
0
19
Order By: Relevance
“…Besides that, central obesity was detected in more than half of the participants. With regard to these risk factors, our results are more similar to the findings of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) living in North America [50] and to a recent study conducted in the Southern cone of Latin America [51]. Our results suggest that this population is in need of effective public health interventions to manage obesity and prevent further increases of obesity-associated diseases including diabetes, dyslipidemia, hypertension and other CVDs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Besides that, central obesity was detected in more than half of the participants. With regard to these risk factors, our results are more similar to the findings of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) living in North America [50] and to a recent study conducted in the Southern cone of Latin America [51]. Our results suggest that this population is in need of effective public health interventions to manage obesity and prevent further increases of obesity-associated diseases including diabetes, dyslipidemia, hypertension and other CVDs.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results with regard to BMI were found in other studies where men showed higher prevalence of overweight and obesity [47,65]. The study of Rubinstein et al, (2015), in the Southern cone of Latin America, reported that women showed higher prevalence of obesity, abdominal obesity, risky LDL-C, and MS compared with men [51]. In our study, men showed unhealthier lifestyle habits than women, namely alcohol intake and low consumption of fruit and vegetables.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A detailed description of the study population and design has been presented elsewhere. 15 Briefly, the CESCAS I study used a 4-stage multistage random sample of a general population of 7,524 adults aged 35–74 years from four mid-sized cities in Argentina (Bariloche and Marcos Paz), Chile (Temuco) and Uruguay (Canelones-Barros Blancos). In the first stage, census radii were randomly selected from each of the four locations, stratified by socio-economic level.…”
Section: Methodsmentioning
confidence: 99%
“…Like other low-income and middle-income countries (LMICs), Argentina’s systemic challenges to improving the detection and management of CVD include low rates of awareness, shortages of trained healthcare workers to provide services, overcrowded primary care centres (PCCs) and overall lack of resources in healthcare systems 3. Hypertension, one of the primary, modifiable risk factors for CVD, has been shown to be controlled for only 20% of Argentinians 4. In order to reduce the CVD burden in Argentina through programmes such as REDES, a high priority is to determine ways to increase screening in community settings along with efficient referral to PCCs for proper management of the disease, using task-shifting5 and mHealth technologies 6…”
Section: Introductionmentioning
confidence: 99%